Development and Application of Serious Games for Teaching Chemical Kinetics - Lima, Thamyla Maria de Sousa (2020)
The complexity of a non-linear character that represents the act of teaching does not allow the teacher to resort to a single way of approaching the process of education in higher education. In other words, contemporary society filled with information technologies with a high degree of interactivity requires from teachers a greater understanding and search for different motivational forms and mechanisms for students. In this context, the work addresses the use of digital games as a tool for interaction between students and kinetic chemistry content, as an alternative methodology of the teaching and learning process. For this purpose, an interactive board (Edutable), logical management software and a mobile application were designed and built during the work. Then, based on the usability method, task success studies and positive usability experience were performed. The results of the evaluations showed that, in the users' perception, the board game complies with the playful and educational character, obtaining scores above 80% on the SUS (System Usability Scale), an evaluation model applied in the present work.